HUMAN CAPITAL PRODUCTIVITY, ENDOGENOUS GROWTH, AND WELFARE: THE ROLE OF UNCERTAINTY. (22nd March 2016) - Diene, Mbaye; Diene, Bity; Azomahou, Théophile T.
Abstract : Several policies or interventions have been implemented in developing countries with the ultimate goal of improving educational outcomes and human capital. Although many empirical studies have pointed to mixed results of these interventions, the role of uncertainty arising from the state of nature about the educational environment and household characteristics in the efficiency of these interventions still lacks an economic mechanism. This paper aims at developing a theoretical framework that links policy interventions to educational outcomes. We characterize optimal policies and determine the conditions for enhancing social welfare.